Pengaruh Motivasi dan Komitmen Organisasi Terhadap Kepuasan Kerja Pada Karyawan Cafe Kopi Dolok Jl. Jenderal Sudirman Kota Tebing Tinggi - Nainggolan, Benhart (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine how the influence of motivation and Organizational Commitment on Job Satisfaction of employees of Cafe Kopi Dolok Jl. Jenderal Sudirman Tebing Tinggi City. Based on the results of observations made by researchers, it is known that there are several problems regarding job satisfaction at the Cafe Kopi Dolok, including motivation and organizational commitment. The research sample used as many as 31 people with saturated sampling method. This research uses a type of quantitative research with nature of replication research. This research is a replication of previous research where the difference lies only in the object studied. The research method uses multiple linear regression analysis. The results of the hypothesis test state that: Hypothesis 1 is accepted, then motivation has an affects on job satisfaction. Hypothesis 2 is accepted, so organizational commitment affects job satisfaction . Hypothesis 3 is accepted, then the variables of motivation and organizational commitment simultaneously affect the job satisfation of employees Cafe Kopi Dolok Jl. Jenderal Sudirman Tebing Tinggi City.